Cyberbullying Experiences on Social Media and Suicide Risk Among Adolescents - Brenda Geralda; Sofwan Indarjo; Efa Nugroho (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The increasing intensity of social media use among adolescents in the digital era has also increased the risk of exposure to cyberbullying, which has fatal impacts on mental health, including the emergence of suicide risk. Adolescents who experience cyberbullying tend to have a higher likelihood of suicidal ideation compared to adolescents who are not exposed to cyberbullying. Globally, suicide has become one of the leading causes of death among individuals aged 15–19 years, with more than 700,000 deaths annually. This study aimed to systematically analyze experiences of cyberbullying on social media and suicide risk among adolescents. This study employed a systematic literature review approach. The literature search was conducted through the ScienceDirect, PubMed, and Google Scholar databases for publications from 2016–2026. Articles identified through the search process were screened based on predetermined inclusion and exclusion criteria. Eligible articles were analyzed using narrative synthesis. Based on 14 included articles, the forms of cyberbullying experiences among adolescents included harsh or hurtful online comments, verbal humiliation on social media, and the spread of digital rumors. These experiences may lead to psychological distress such as depression, anxiety, low self-esteem, feelings of being a burden, and social isolation among adolescents. These conditions contribute to an increased risk of suicide, ranging from suicidal ideation to suicide attempts. In conclusion, the most prevalent experiences of cyberbullying on social media are harassment and denigration which can trigger internal psychological processes in adolescents such as thwarted belongingness and perceived burdensomeness. These psychosocial impacts can manifest as spectrum of suicide risk. Experiences of cyberbullying on social media is a complex mental health problem among adolescents and require comprehensive prevention strategies through digital literacy, psychosocial support, family and school involvement, and the promotion of adolescent mental health.Keywords: adolescent; cyberbullying; mental health; social media; suicide risk